Governance work guidance for financial and institutional reform - الشمري صادق راشد (Journal of Economics and Administrative Sciences, 2012)
There has been increase in banks and financial institutions interest in governance topic, as it focused all it attention on this topic specially after the growing role and massive expansion of the private sector in economic life , this sector become vital and important and basic role in growth and developing countries economy that’s why there been increase interest in governance and its mechanism , using this mechanism ( board of directors mechanism , ownership concentration mechanism , financial compensation mechanism, minimum rate of capital mechanism) who would adjust and guide the path and orientation of banks and financial institutions as to ensure the achievement of their goals and mission of their desired within the framework of banking legislation governing these mechanisms. As there been growing attention in governance after the economic collapse and financial crisis a lot of countries faced during the ninety’s decade from the twentieth century, also after the financial and accounting collapses for many of global companies and what followed bankruptcy for many of banks. Addition to liberating financial market and globalization and technology progress and what follow from fast changes in the global banking environment, as a lot of banks has faced a lot of fluctuations all that lead banking and financial institutions to put great attention on governance topic for the positive effect on the financial and institutional performance and achieve the growth of society and its development.